Highly chemoselective synthesis of hindered amides via cobalt-catalyzed intermolecular oxidative hydroamidation - Yun-Nian Yin (Nature Portfolio, 2021)
α-Tertiary amides are common in bioactive natural products and pharmaceuticals, but challenging to access by conventional methods. Here, the authors report a single-step approach toward α-tertiary amides via cobalt-catalyzed intermolecular oxidative hydroamidation of unactivated alkenes.